Exercise performance over the menstrual cycle in temperate and hot, humid conditions - Janse de Jonge, X. A.; Thompson, M. W.; Chuter, V. H.; Silk, L. N.; Thom, J. M. (Medicine & Science in Sports & Exercise, 2012)
Purpose: This study investigated the effects of the menstrual cycle on prolonged exercise performance both in temperate (20°C, 45% relative humidity) and hot, humid (32°C, 60% relative humidity) conditions.